Biological parameters of Spodoptera cosmioides Walker (Lepidoptera: Noctuidae) in cotton varieties* - Araujo, Carolina Rodrigues De; Busoli, Antonio Carlos [UNESP] (Instituto Biológico, 2020)
Spodoptera cosmioides Walker is a polyphagous insecticide-resistant species found in various regions of Brazil. Despite occurring at low densities, it is considered a potential pest of cotton, soybean, and bean crops in the Brazilian cerrado. This work investigated the comparative biology of S. cosmioides in the commercial transgenic cotton NuOPAL (Bollgard I, Evento 531) and the conventional isoline variety DeltaOPAL. The experiment was conducted under laboratory conditions (26 ± 1°C; relative humidity: 70 ± 10%; photoperiod: 12h), using newly-hatched and individualized larvae. We evaluated the duration and viability of immature stages, duration of the biological cycle, pupal weight, sex ratio, percentage of deformed adults and of adults trapped in the pupal case, adult longevity, fecundity, and egg viability. The biological parameters observed showed no significant differences between the two varieties studied, which enabled high consumption, high assimilation, high fecundity, and viability for S. cosmioides.

Spodoptera cosmioides Walker é uma espécie polífaga, resistente a inseticidas em várias regiões do país e, apesar de ocorrer em baixas densidades, é considerada uma praga potencial para as culturas de algodão, soja e feijão no cerrado. Neste trabalho, estudou-se a biologia comparada de S. cosmioides sobre o cultivar transgênico comercial de algodoeiro NuOPAL (Bollgard I, Evento 531) e sobre o cultivar isolinha convencional DeltaOPAL. O experimento foi desenvolvido em condições de laboratório (26 ± 1°C; UR: 70 ± 10%; fotofase: 12h) a partir de lagartas recém-eclodidas e individualizadas. Foram avaliados a duração e a viabilidade das fases imaturas, a duração do ciclo biológico, o peso de pupas, a razão sexual, a porcentagem de deformação de adultos e de adultos não liberados dos invólucros pupais, a longevidade de adultos, a fecundidade e viabilidade de ovos. Os parâmetros biológicos observados não diferiram significativamente em relação às duas cultivares, que proporcionaram alto consumo, alta assimilação, alta fecundidade e viabilidade à S. cosmioides.
Parâmetros biológicos de Spodoptera cosmioides Walker (Lepidoptera: Noctuidae) em variedades de algodoeiro
Keywords: Gossypium hirsutum; transgenic plants; Bollgard; CryIAc; Gossypium hirsutum; planta transgênica; Bollgard; CryIAc